Uji Sitotoksik Ekstrak Etanol Fraksi Polar, Semipolar, Dan Nonpolar Daun Jambu Biji (Psidium guajava L.) Terhadap Sel Kanker Kolon WiDr - Maharani, Aprilia Shinta, Maryati, Ph.D., Apt (2017)
Colon cancer is one of the common causes of death that comes from the transformation of normal intestinal epithelial adenomatous polyps and invasive cancer. Surgery, chemotherapy, and radiotherapy is the method used in the treatment of cancer. Although it shows the success of therapy, side effects in the use of drugs is still quite dangerous, so should be developed with herbal medicine. Guava leaf (Psidium guajava L.) is a plant that can be developed as an anticancer agent. The purpose of this study was to determine the cytotoxic effect of ethanol extract, fractions polar, semipolar and nonpolar guava leaves against WiDr colon cancer cells and determine classes of compounds contained in the sample had the most excellent IC50. Extraction methods on research done by maceration method with 96% ethanol. Fractionation was conducted using liquid-liquid partition with penyari n-hexane, ethyl acetate, and ethanol-water. Cytotoxic test was conducted by MTT assay. Phytochemical screening was conducted using thin layer chromatography. Results IC50 ethanol extract of guava leaves is 183,888 µg / mL and IC50 fraction of polar, semipolar and nonpolar greater than 250 µg / mL. Thin layer chromatography test results showed that ethanol extracts contain class of flavonoids, tannins, saponins, alkaloids and polyphenols.